Development of LMS-Based E-Learning for Physical Education Learning in Binjai City - Ningsih, Sri Wahyuni Retno; Dewi, Rahma; Irfan, M. (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2025)
This study aims to develop an LMS-based e-learning product for PJOK learning in Binjai City. This study aims to develop an LMS-based e-learning product for PJOK learning in Binjai City. The methodology used is research and development. The sample was selected using total sampling, comprising 50 seventh-grade students from SMPN 1 Binjai's class VII. The results of the study on a small-scale trial of the level of feasibility of the learning application product 4.4 out of 5.0 are included in the